Strengthening Ghana’s Banking Security through IoT: Implications for Achieving SDG Goals - Adade Sedom, Percy; Emmanuel Ofotsu, Kwesi Bannor; Doris, Enimil; Khan Sarfaraz, Ali; Ida, Hindarsah (INTI International University, 2025)
The use of the Internet of Things (IoT) in Ghana's banking sector has enormously enhanced efficiency in operations and customer service delivery. The digitalization process, however, poses considerable cybersecurity threats. This study investigates the impact of IoT on Ghanaian banks' cybersecurity with emphasis on the prominent risks, challenges, and strategic interventions. According to secondary data extracted from top banking reports and qualitative analysis by IT security professionals, we have prevalence of threats such as distributed denial-of-service (DDoS) attacks, unauthorised access, and data breaches. The findings quote the highest priority need for robust cybersecurity measures, continuous risk assessment, and government-initiated regulatory structures to offset risks of IoT deployments in financial institutions. The findings reference the greatest need for efficient cybersecurity measures, continued risk evaluation, and regulatory-driven frameworks being initiated by governments in order to offset vulnerabilities of IoT installations in financial institutions It is in line with Sustainable Development Goal 9 (Industry, Innovation, and Infrastructure), SDG 11 (Sustainable Cities and Communities), and SDG 16 (Peace, Justice, and Strong Institutions), as regards providing safe, resilient, and secure financial environments